2002
DOI: 10.1038/ni850
|View full text |Cite
|
Sign up to set email alerts
|

Wnt glycoproteins regulate the expression of FoxN1, the gene defective in nude mice

Abstract: T cell development and selection require the fully mature and diverse epithelial microenvironment of the thymus. Acquisition of these characteristics is dependent on expression of the forkhead (also known as winged-helix) transcription factor FoxN1, as a lack of functional FoxN1 results in aberrant epithelial morphogenesis and an inability to attract lymphoid precursors to the thymus primordium. However, the transcriptional control of Foxn1 expression has not been elucidated. Here we report that secreted Wnt g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
248
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(257 citation statements)
references
References 46 publications
7
248
1
1
Order By: Relevance
“…Despite expression of Lef1, nuclear translocation of β-catenin, indicating activation of the WNT pathway, was not observed in the epithelium of the most affected mutant follicles, suggesting that WNT pathway activation lies downstream of epithelial BMPR1A signaling. The recent identification of Foxn1 as a direct WNT target gene (Balciunaite et al, 2002) suggests that BMPR1A might regulate Foxn1 expression by dual mechanisms: activation of WNT signaling and induction of Msx expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite expression of Lef1, nuclear translocation of β-catenin, indicating activation of the WNT pathway, was not observed in the epithelium of the most affected mutant follicles, suggesting that WNT pathway activation lies downstream of epithelial BMPR1A signaling. The recent identification of Foxn1 as a direct WNT target gene (Balciunaite et al, 2002) suggests that BMPR1A might regulate Foxn1 expression by dual mechanisms: activation of WNT signaling and induction of Msx expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this protective effect, administration of FGF7 has been shown to directly improve thymic function af-ter bone marrow transplantation (Panoskaltsis-Mortari et al, 1998;Min et al, 2002;Alpdogan et al, 2006) and can partially reverse the loss of thymic function associated with agerelated thymic involution (Alpdogan et al, 2006;Min et al, 2007). A detailed analysis of the response of TE to a single course of thee injections of FGF7 to adult mice revealed transient alterations that included the elaboration of chemokines involved in recruitment of progenitor cells to the thymus, stimulated TE proliferation, and elevated expression of molecules that participate in the Wnt and BMP signaling pathways (Rossi et al, 2007b) previously implicated in the development of TE (Balciunaite et al, 2002;Bleul and Boehm, 2005). The increased thymic cellularity observed after transient administration of FGF7 and in lckFGF10 TG mice transplanted with WT bone marrow may actually be the result of similar responses that differ in the magnitude of the progenitor TE pool involved.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling has been implicated in the regulation of Foxn1 expression (Balciunaite et al, 2002), while signaling pathways that regulate NFkB activity are known to play an important role in the development of a functional medullary TE compartment (Burkly et al, 1995;Boehm et al, 2003;Rossi et al, 2007c). Signaling mediated by bone morphogenetic proteins (BMPs) and fibroblast growth factors (FGFs) has also been implicated in proper TE differentiation (Erickson et al, 2002;Jenkinson et al, 2003;Bleul and Boehm, 2005;Rossi et al, 2007c).…”
Section: Introductionmentioning
confidence: 99%
“…[79][80][81][82] Conversely, Fz receptors are expressed primarily by the thymocytes, but also by stromal cells. 79 79 Recently, our group has shown that mainly DN1-3 thymocytes undergo Wnt signaling.…”
Section: Notch and Wnt Signaling In T-cell Development And T-allmentioning
confidence: 99%